Gambaran Pengetahuan Perawat Tentang BHD Di Rumah Sakit Santa Elisabeth Medan Tahun 2023 - Rusmauli Lumban Gaol; Petronella Purba; Indra Hizkia (Jurnal Anestesi, 2023)
Basic life support Basic life support (BHD) is an action or effort made to prolong life for sufferers whose lives are threatened. This study aims to determine the definition, purpose, indications and management of basic life support at Santa Elisabeth Hospital Medan. This type of research is descriptive with a total population of 250. Sampling is carried out using a purposive technique, with a total of 71 respondents. The results show that the knowledge of nurses at Santa Elisabeth Hospital Medan is in good category, 54 respondents (76.1%), 13 respondents (18.3%) sufficient, and 4 respondents (5.6%) lacking. It can be concluded from the study that the majority of nurses are categorized as "good". The definition of basic life support is categorized as good with the number of respondents 52 or (73.2%), enough 11 respondents (15.5%) and less 8 respondents (11.3%). In this research, basic life support goals can be categorized in the "good" category with 40 respondents (56.3%) being good, 25 respondents (35.2%) sufficient, and 6 respondents (8.5%) lacking. Indications for basic life support are categorized as "good" with a good number of respondents 61 (85.9%) and less than 10 respondents (14.1). management of basic life support can be categorized as "good" with the number of good respondents 48 respondents (67.6%), enough 18 respondents (25.4%) and less 5 (7.0%). Nurses at Santa Elisabeth Medan Hospital have quite good knowledge because there is support from basic life support training or BTCLS.